The Effects of Early Marriages on Child Development in Uganda: A Case Study of Rukungiri District Local Government Probation Office - Moreen Ahimbisibwe (Uganda Christian University, 2024)
The study on the effects of early marriage on child development was conducted in Rukugiri district local government through the probation office. The present study aimed at investigating the effects of early marriages on child development in Uganda because various research endeavors had been undertaken to determine the primary cause of early marriages on child development; however, no definitive evidence of a solution to address its effects has been established. Despite the extensive exploration of early marriages and their impact on child development in Uganda, there remained a notable gap in the existing literature regarding the long-term psychological and socio-economic effects of early marriages on children within the Ugandan context. While past studies had addressed related issues, there was need for a more comprehensive examination of the specific research goals of the current study, particularly in terms of understanding the nuanced and multifaceted impacts of early marriages on child development in Uganda. The search chose the case study research design because it was the most suited for the problem she was investigating. The selection of this specific research design was warranted by the requirement for specific, detailed, and contextual knowledge regarding the subject under investigation.A simple random sampling strategy was used by the researcher and by which, 44 respondents were selected for the study. Thus, when all factors taken into account, the findings unequivocally showed that early child marriages seriously impair the expectations and dreams of the victims for the future, as well as having a negative effect on children's development. Practically speaking, it was found that the national government does not have any programs specifically created to address social issues such as early child marriages in the communities. However, additional investigation into how to address early marital exposure with a gender-balanced approach has to be done. That for instance, it needs to be determined whether all of the young women who marry off too soon are wedded to older men, or whether there is an ignorance about young females being coerced into marrying younger boys.